Tradition and trade: culture and exploitation of avian fauna by a rural community surrounding protected areas in the south of Bahia's State, Northeastern Brazil - Antonio Iderval Sodré Neto; Ricardo Evangelista Fraga; Alexandre Schiavetti (BMC, 2022)
Abstract Background Illegal capture and trade of wild birds are some of the most present types of wildlife trade in Brazil, and are often associated with cultural and socioenvironmental aspects. Those habits are particularly present in rural communities, where bird trade can be a source of income in dire economic situations and bird-keeping is a cultural trait passed down from generations. Methods We conducted a series of semi-structured interviews with bird-keepers and traders within the surrounding region of the Parque Nacional de Boa Nova, inquiring about local customs and practices related to bird-keeping, bird trade and bird capture, as well as how these were affected by the establishment of protected areas nearby. We then outlined the main trends and perceptions in a quantitative and a qualitative approach. Results A total of 21 avian species were mentioned as being used as pets and in commercialization, contests and breeding, most of them occurring naturally in the region. Most respondents were men possessing low levels of education and income. We observed a series of specialized practices regarding bird-keeping, from basic maintenance of captive individuals in order to ensure the animal's health, to interspecies breeding as to produce hybrid individuals. Mentioned methods used to capture wild birds often involved specialized traps and were conducted mainly within the national park's area. Bird trade was said to occur mostly in urban settlements, and the value of captive birds was said to vary, based on species and beforehand training. The official establishment of the protected area impaired all practices related to bird-keeping and trade, mostly as a result of increased surveillance by environmental agencies. Conclusion The collected information presents a series of specialized habits and practices involved in bird-keeping, bird capture and bird trade, many of them being associated with the local avifauna surrounding the region. The establishment of protected areas affected local perceptions regarding bird-keeping and related practices mostly through fear of penalty, although individuals demonstrated some knowledge about how to evade surveillance. We recommend further studies about effective ways to integrate local communities in nearby protected areas' conservation.